Analisis Frekuensi Natural Rangka Main Landing Gear Pesawat UAV Menggunakan Ansys Workbench - Wibawa, Lasinta Ari Nendra (Jurnal Mesin Nusantara, 2022)
The main landing gear is one of the important components in UAV aircraft. This paper aims to analyze the natural frequency of the main landing gear and determine its normal mode shape. This analysis is important so that no resonance causes damage to the main landing gear components. The main landing gear uses Aluminum 6061 material and the analysis is carried out using the finite element method with the help of Ansys Workbench software. The analysis showed that the natural main landing gear frequencies for mode 1 to mode 6 were 76.04 Hz, 85.07 Hz, 167.82 Hz, 201.92 Hz, 288.39 Hz, and 327.00 Hz, respectively. The maximum deformation of the main landing gear for mode 1 to mode 6 is 33.73 mm, 35.35 mm, 48.16 mm, 44.62 mm, 38.14 mm, and 41.51 mm, respectively.